Virtual versus face-to-face teaching: an approach in implementing blended learning among first year BDS students in UiTM / Nurhaslina Hasan ... [et at.] - Hasan, Nurhaslina; Sabirin, Faezah; Ahmad, Vivi Noryati (UiTM Press, 2017)
Nowadays, any students are well-exposed to digital technology. Since blended learning incorporates digital elements into teaching, this method is thought to be suitable for this todays’ generation. The virtual teaching was therefore introduced alongside the face to face teaching to increase students experience and understanding in learning process. This study was designed to compare the effectiveness between virtual and face to face teaching of first year dental (BDS) student on their understanding of Physiology. All 70 BDS students took part in this study. Two modules from their syllabus with five lectures each were selected. In the first module, the five lectures were delivered face to face. In another module, the five lectures were delivered virtually using E-Learning softwares that were displayed in the classroom during lecture times. At completion of all lectures in each module, all students are subjected to answer a quiz containing 100 true/ false questions. The data collected were then analysed using SPSS version 22. A short survey was then conducted to gather feedbacks on student acceptance and preference. The mean marks of face to face and virtual teachings were 70.57+ 4.80 and 71.69+5.61 respectively. The difference between the two however was not significant. From the survey, the students generally accepted the virtual teaching but preferred the face to face teaching. Therefore the virtual teaching method can be implemented as early as in the first year without worry on jeopardizing their grades. In conclusion, with some betterment on the virtual teaching method such as inclusion of two-way interactions would improve their understanding in learning Physiology thus may help the students in getting better grades.